Analysis of SIMBA’s Implementation Regarding the Effectiveness of BAZNAS Bogor District Zakat Management - Ramadhan, Muhammad Alif; Mukhlisin, Murniati (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2025)
Abstract. This study aims to evaluate the implementation and effectiveness of SIMBA at BAZNAS Bogor Regency, as well as the effectiveness of zakat management. Using a qualitative case study approach, data was collected through interviews and literature study. SIMBA’s effectiveness was measured using DeLone and McLean’s information system (D&M IS) success model, while the effectiveness of zakat management was measured using the allocation to collection ratio (ACR) method. The results show that SIMBA is effective in supporting zakat management, with features that facilitate access to accurate and timely information. Zakat management is also considered effective, with a positive ACR average. Despite technical glitches, users express strong satisfaction with SIMBA, especially regarding its convenience, transparency, and enhanced accountability. Keywords: SIMBA, BAZNAS Bogor Regency, D&M IS Success, ACR